Pembentukan Karakter Peduli Lingkungan Melalui Program Sekolah Berbasis Ekologi di SMA Muhammadiyah Kota Jayapura - Puguh Sujarta; Suharno Suharno; Maria L. Simonapendi; Suriani Br. Surbakti; Sriyanto Sriyanto; Farmawaty Farmawaty (Jurusan Biologi FMIPA Universitas Cenderawasih, 2026)
Character building is a vital component of education, aimed at fostering a generation of individuals of noble character, discipline, and responsibility through internal and external strategies. The objectives of this community service activity are: (a) to provide understanding, foster attitudes, and bring about behavioural changes that demonstrate care for the environment; (b) through this community service activity, it is hoped that an accredited national community service journal will be produced. The community service was carried out on 11 May 2026 using lectures, simulations, practical sessions, and documentation. The results of the community service showed that 26 people attended the event, whilst only 23 respondents completed the questionnaire. Survey results showed that 73.9% of respondents answered ‘know’, 26.1% ‘do not know’, and 4.3% were ‘unsure’ regarding their knowledge of ecology and the environment. Environmental awareness was recorded at 82.6% of respondents, whilst active participation was only 52.2% of respondents. The activity evaluation results showed a range of 43%–81%, indicating that participants possessed adequate knowledge of ecology and the environment. Overall, the activity was deemed successful and capable of fostering positive character traits in participants to enhance their environmental awareness. The conclusions are that (1) participants were very enthusiastic about taking part in community service activities and understood the material on character building for environmental care through the Ecology-Based School Programme; (2) based on the evaluation results.